Life-Threatening Intrapulmonary Hemorrhage due to Vancomycin-Induced Thrombocytopenia: A Case Report - Haneen Abdalhadi; Yazan Fahmawi; Abhijin Das; Brian Fouty (Case Reports in Critical Care)
Thrombocytopenia is a rare and sometimes life-threatening complication of Vancomycin. A 52-year-old male patient with acute kidney injury was treated with Vancomycin for ventilator-associated pneumonia. Three days later, his platelets decreased from 172×109/L to 3×109/L over a 36-hour period. The patient developed significant intrapulmonary bleeding leading to profound hypoxemia. Workup was negative for thrombotic thrombocytopenic purpura, disseminated intravascular coagulopathy, atypical hemolytic uremic syndrome, heparin-induced thrombocytopenia, and autoimmune diseases. All recently started medications were discontinued, and the patient was started empirically on methylprednisolone and intravenous immunoglobulin. The patient’s platelets increased, and his airway bleeding stopped within 48 hours; his platelet count returned to normal by 18 days. Vancomycin-dependent anti-platelet antibodies were identified in the patient’s serum by flow cytometry. Thrombocytopenia is an underrecognized complication of Vancomycin that can lead to life-threating bleeding. Stopping Vancomycin may be sufficient to reverse the thrombocytopenia in patients with normal renal function, but more aggressive measures such as steroids, IVIG, and dialysis may be required to stop bleeding and reverse thrombocytopenia in patients with underlying kidney injury who cannot effectively excrete Vancomycin.